Ethical Analyses of HRM: A Review and Research Agenda - Greenwood, Michelle (2013)
The very idea of human resource management raises ethical considerations: What does it mean to us as humans for human beings to be managed as resources? Intriguingly, the field of ethics and HRM remains underdeveloped. Current approaches to HRM fail to place ethical considerations as their central warrant. This article, building on Greenwood (J Bus Ethics 36(3):261–279, 2002), argues for a deeper analysis of ethical issues in HRM, indeed for a differentiated ethical perspective of HRM that sets normative deliberations as its prime task. By identifying a distinct ethical approach to HRM that is unashamedly normative and socio-politically embedded, two objectives can be achieved. First, mainstream and critical approaches will be challenged to take ethical issues in HRM more seriously. Second, a dedicated forward-looking research agenda for the ethical analysis of HRM will be advanced.
Keywords: Socio-political; Normative; HRM theory; theoretical perspectives; Critical HRM; Ethical HRM